Enteropathic histopathological features may be associated with Shwachman–Diamond syndrome. Issue 7 (24th May 2010) - Shah, N; Cambrook, H; Koglmeier, J; Mason, C; Ancliff, P; Lindley, K; Smith, V V; Bajaj-Elliott, M; Sebire, N J
Abstract : Aim: To review the gastrointestinal mucosal histological features of biopsies from children with Shwachman–Diamond syndrome (SDS) examined at a single specialist centre. Methods: Search of a clinical database was performed to identify SDS cases and their gastrointestinal biopsies were reviewed for morphological parameters such as crypt:villous ratio, crypt hyperplasia and abnormal inflammatory infiltrates. Histological sections were also immunostained with CD4, CD20 and HLA-DR to determine the nature of the inflammatory infiltrate. Results: 15 SDS cases were included, 7 (47%) of which showed morphologically normal duodenal villous architecture, whereas 8 (53%) showed varying degrees of enteropathic histological features ranging from villous blunting to partial villous atrophy and duodenitis. 11/15 (73%) showed some degree of duodenal inflammation, including increased lamina propria density of plasma cells, macrophages and eosinophils. Conclusion: Varying degrees of duodenal inflammatory enteropathic features are present in more than 50% of symptomatic children with SDS. This suggests that, in addition to pure pancreatic exocrine failure, an enteropathic component may contribute to symptoms in some cases, and be potentially responsive to appropriate therapy.